Institutional Strategies to Increase Retention Indigenous Papuan Students (OAP) At Musamus University - Maria Fransina Yawiwa; Cepi Safruddin Abd Jabar (Didaktika: Jurnal Kependidikan, 2025)
StudyThis study uses a qualitative approach with a case study design to explore the institutional strategies implemented by Musamus University to increase retention of Indigenous Papuan (OAP) students. Data collection methods included semi-structured interviews and focus group discussions (FGDs) with 15-20 Indigenous Papuan students selected through purposive sampling. The data were analyzed using Voyant Tools to identify key patterns and themes in students' perceptions of institutional support.ResultsResearch shows that non-academic students respond positively to program orientations that help them adapt to the academic environment. Academic support, such as tutoring and access to educational resources, is considered crucial to their academic success. Furthermore, active involvement in the campus community increases students' sense of belonging to the university, which contributes to increased retention. Discussionrevealed that strategies involving financial support through scholarships, as well as moral and academic mentoring, are essential for increasing student motivation. Data analysis also showed that positive interactions between students and lecturers play a crucial role in creating a supportive learning environment. Recommendations from this study include developing a more comprehensive scholarship program, improving moral support, and adapting educational programs to better suit the needs of indigenous students. In conclusionMusamus University plays a crucial role in creating an inclusive and supportive academic environment for Indigenous Papuan students. By implementing a holistic institutional strategy, the university can not only improve student retention but also contribute to the empowerment of the Indigenous Papuan community as a whole. This research is expected to serve as a reference for better education policies in the future.